광픽업 유닛 기반 원자현미경의 Dynamic 모드 측정용 Lock-in Amplifier - Mark A. Cruz; 송수환(Su-Hwan Song); 이상헌(Sang Heon Lee) (한국생산제조학회지, 2019)
In this paper, we introduce a lock-in amplifier for the dynamic mode operation of atomic force microscopy, based on the optical pickup unit of a DVD. We fabricated a lock-in amplifier, which is fundamentally based on the principle of the dual phase mode, and included an additional enhancement structure to ensure high bandwidth, so that it is capable of supporting high-speed scanning probe microcopy in the future. We performed a basic experiment for performance evaluation and dynamic mode imaging of a standard sample by applying the fabricated lock-in amplifier module to a pre-developed optical pickup unit based atomic force microscopy. KCI Citation Count: 0